Low carbon, high growth : Latin American response to climate change : an overview - de la Torre, Augusto (IBRD WashingtonUS, 2009)
Addresses a number of questions related to the causes and consequences of climate change in Latin America. Contributes new information and analysis to help inform the public policy debate on this important issue.